Oral medications for the treatment of postural orthostatic tachycardia syndrome; a systematic review of studies before and during the COVID-19 pandemic - Pierson, Benjamin C.; Apilado, Kyle; Franzos, M. Alaric; Allard, Rhonda; Mancuso, James D.; Tribble, David; Saunders, David; Koehlmoos, Tracey Perez (Frontiers in Neurology, 2025)
BackgroundPostural Orthostatic Tachycardia Syndrome (POTS) is a complex form of dysautonomia that presents with abnormal autonomic reflexes upon standing, leading to symptoms such as lightheadedness, tachycardia, fatigue, and cognitive impairment. The COVID-19 pandemic has brought renewed attention to POTS due to its overlap with post-acute sequelae of COVID-19 (PASC). Studies have found that a substantial percentage of COVID-19 survivors exhibit symptoms resembling POTS, elevating POTS diagnoses to previously unseen levels. We systematically reviewed the literature for existing high-quality evidence on potential interventions.MethodsA systematic review of the literature was performed to identify studies of oral medications for the management of POTS. We searched for published manuscripts on the medical management of POTS through 6 April 2024 which met pre-specified inclusion criteria. We conducted quality appraisal and assessed risk of bias before extracting the data and performing synthesis to determine the current state of the evidence; particularly in the context of PASC.ResultsThe study search and selection process identified 32 studies that met inclusion criteria, comprising randomized controlled trials, observational studies, and systematic reviews. Most included studies were judged to be of moderate to high quality, with largely low risk of bias. The most frequently studied medications were beta-blockers, ivabradine, and midodrine. Ivabradine and midodrine demonstrated the highest rate of symptomatic improvement, while beta-blockers showed the largest reduction in heart rate variability. Limited evidence was available for PASC-associated POTS, but findings suggest that treatments may have similar efficacy in both PASC and non-PASC cases.ConclusionIvabradine, midodrine, and beta-blockers currently appear to be reasonable front-line choices in pharmacologic management of POTS (PASC associated and otherwise). Further RCTs that evaluate long term outcomes of medications are needed to further establish evidence based pharmacologic treatment approaches for POTS. Particular areas of inquiry include differential efficacy of recommended therapies based on POTS subtypes, and a need for treatments directly targeting the underlying autonomic nervous system dysfunction.Systematic review registrationPROSPERO, identifier CRD42024505967, https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=505967.